Brief Announcement: Hashed Predecessor Patricia Trie - A Data Structure for Efficient Predecessor Queries in Peer-to-Peer Systems - Kniesburges, Sebastian; Scheideler, Christian (Proceedings of the 26th International Symposium on Distributed Computing (DISC))
The design of ecient search structures for peer-to-peer systems has attracted a lot of attention in recent years. In this announcement we address the problem of nding the predecessor in a key set and present an ecient data structure called hashed Predecessor Patricia trie. Our hashed Predecessor Patricia trie supports PredecessorSearch(x) and Insert(x) and Delete(x) in O(log log u) hash table accesses when u is the size of the universe of the keys. That is the costs only depend on u and not the size of the data structure. One feature of our approach is that it only uses the lookup interface of the hash table and therefore hash table accesses may be realized by any distributed hash table (DHT).

Basic Network Creation Games with Communication Interests - Cord-Landwehr, Andreas; Huellmann (married name: Eikel), Martina; Kling, Peter; Setzer, Alexander (Proceedings of the 5th International Symposium on Algorithmic Game Theory (SAGT))
Network creation games model the creation and usage costs of networks formed by a set of selfish peers.Each peer has the ability to change the network in a limited way, e.g., by creating or deleting incident links.In doing so, a peer can reduce its individual communication cost.Typically, these costs are modeled by the maximum or average distance in the network.We introduce a generalized version of the basic network creation game (BNCG).In the BNCG (by Alon et al., SPAA 2010), each peer may replace one of its incident links by a link to an arbitrary peer.This is done in a selfish way in order to minimize either the maximum or average distance to all other peers.That is, each peer works towards a network structure that allows himself to communicate efficiently with all other peers.However, participants of large networks are seldom interested in all peers.Rather, they want to communicate efficiently with a small subset only.Our model incorporates these (communication) interests explicitly.Given peers with interests and a communication network forming a tree, we prove several results on the structure and quality of equilibria in our model.We focus on the MAX-version, i.e., each node tries to minimize the maximum distance to nodes it is interested in, and give an upper bound of O(\sqrt(n)) for the private costs in an equilibrium of n peers.Moreover, we give an equilibrium for a circular interest graph where a node has private cost Omega(\sqrt(n)), showing that our bound is tight.This example can be extended such that we get a tight bound of Theta(\sqrt(n)) for the price of anarchy.For the case of general networks we show the price of anarchy to be Theta(n).Additionally, we prove an interesting connection between a maximum independent set in the interest graph and the private costs of the peers.

Approximate Duality of Multicommodity Multiroute Flows and Cuts: Single Source Case - Kolman, Petr; Scheideler, Christian (Proceedings of the 23th ACM SIAM Symposium on Discrete Algorithms (SODA))
Given an integer h, a graph G = (V;E) with arbitrary positive edge capacities and k pairs of vertices (s1; t1); (s2; t2); : : : ; (sk; tk), called terminals, an h-route cut is a set F µ E of edges such that after the removal of the edges in F no pair si ¡ ti is connected by h edge-disjoint paths (i.e., the connectivity of every si ¡ ti pair is at most h ¡ 1 in (V;E n F)). The h-route cut is a natural generalization of the classical cut problem for multicommodity °ows (take h = 1). The main result of this paper is an O(h722h log2 k)-approximation algorithm for the minimum h-route cut problem in the case that s1 = s2 = ¢ ¢ ¢ = sk, called the single source case. As a corollary of it we obtain an approximate duality theorem for multiroute multicom-modity °ows and cuts with a single source. This partially answers an open question posted in several previous papers dealing with cuts for multicommodity multiroute problems.

A Self-Stabilization Process for Small-World Networks - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of the 26th IEEE International Parallel and Distributed Processing Symposium (IPDPS))
Small-world networks have received significant attention because of their potential as models for the interaction networks of complex systems. Specifically, neither random networks nor regular lattices seem to be an adequate framework within which to study real-world complex systems such as chemical-reaction networks, neural networks, food webs, social networks, scientific-collaboration networks, and computer networks. Small-world networks provide some desired properties like an expected polylogarithmic distance between two processes in the network, which allows routing in polylogarithmic hops by simple greedy routing, and robustness against attacks or failures. By these properties, small-world networks are possible solutions for large overlay networks comparable to structured overlay networks like CAN, Pastry, Chord, which also provide polylogarithmic routing, but due to their uniform structure, structured overlay networks are more vulnerable to attacks or failures. In this paper we bring together a randomized process converging to a small-world network and a self-stabilization process so that a small-world network is formed out of any weakly connected initial state. To the best of our knowledge this is the first distributed self-stabilization process for building a small-world network.

Competitive and Fair Medium Access Despite Reactive Jamming - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (2011 International Conference on Distributed Computing Systems, ICDCS 2011, Minneapolis, Minnesota, USA, June 20-24, 2011)

Towards jamming-resistant and competitive medium access in the SINR model - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 3rd ACM workshop on Wireless of the students, by the students, for the students, S3@MOBICOM 2011, Las Vegas, NV, USA, September 19 - 23, 2011)

Self-stabilizing leader election for single-hop wireless networks despite jamming - W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Proceedings of the 12th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2011, Paris, France, May 16-20, 2011)

Re-Chord: a self-stabilizing chord overlay network - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (SPAA 2011: Proceedings of the 23rd Annual ACM Symposium on Parallelism in Algorithms and Architectures, San Jose, CA, USA, June 4-6, 2011 (Co-located with FCRC 2011))

Hashed Patricia Trie: Efficient Longest Prefix Matching in Peer-to-Peer Systems - Kniesburges, Sebastian; Scheideler, Christian (WALCOM: Algorithms and Computation - 5th International Workshop, WALCOM 2011, New Delhi, India, February 18-20, 2011. Proceedings)

Programming for Distributed Computing: From Physical to Logical Networks - Scheideler, Christian; Graffi, Kalman (Computer Science, The Hardware, Software and Heart of It)

Broadcasting - How Can I Quickly Disseminate Information? - Scheideler, Christian (Algorithms Unplugged)

Algorithms Unplugged - Vöcking, Berthold; Alt, Helmut; Dietzfelbinger, Martin; Reischuk, Rüdiger; Scheideler, Christian; Vollmer, Heribert; Wagner, Dorothea

Towards Duality of Multicommodity Multiroute Cuts and Flows: Multilevel Ball-Growing - Kolman, Petr; Scheideler, Christian (28th International Symposium on Theoretical Aspects of Computer Science, STACS 2011, March 10-12, 2011, Dortmund, Germany)

Lokale Online-Strategien zur linearen Anordnung von Teilnehmern in einem Peer-to-Peer Netzwerk - Setzer, Alexander

Implementierung eines Verfahrens zur Lösung des 3-Mincut-Problems - Sascha, Brauer

Stabilizing consensus with the power of two choices - Doerr, Benjamin; Goldberg, Leslie Ann; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Proceedings of the 23rd ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In the standard consensus problem there are n processes with possibly di®erent input values and the goal is to eventually reach a point at which all processes commit to exactly one of these values. We are studying a slight variant of the consensus problem called the stabilizing consensus problem [2]. In this problem, we do not require that each process commits to a ¯nal value at some point, but that eventually they arrive at a common, stable value without necessarily being aware of that. This should work irrespective of the states in which the processes are starting. Our main result is a simple randomized algorithm called median rule that, with high probability, just needs O(logmlog log n + log n) time and work per process to arrive at an almost stable consensus for any set of m legal values as long as an adversary can corrupt the states of at most p n processes at any time. Without adversarial involvement, just O(log n) time and work is needed for a stable consensus, with high probability. As a by-product, we obtain a simple distributed algorithm for approximating the median of n numbers in time O(logmlog log n + log n) under adversarial presence.

Self-Stabilizing DeBruijn Networks - Richa, Andrea W.; Scheideler, Christian (Proceedings of the 13th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
This paper presents a dynamic overlay network based on the De Bruijn graph which we call Linearized De Bruijn (LDB) network. The LDB network has the advantage that it has a guaranteed constant node degree and that the routing between any two nodes takes at most O(log n) hops with high probability. Also, we show that there is a simple local-control algorithm that can recover the LDB network from any network topology that is weakly connected.

Robust Distributed Computation in Dynamic Networks - Brandes, Philipp

PeerfactSim.KOM: A PSP System Simulator - Experiences and Lessons Learned - Graffi, Kalman (Proceedings of the IEEE International Conference on Peer-to-Peer Computing (IEEE PsP))
Research on peer-to-peer (p2p) and distributed systems needs evaluation tools to predict and observe the behavior of protocols and mechanisms in large scale networks. PeerfactSim.KOM is a simulator for large scale distributed/p2p systems aiming at the evaluation of interdependencies in multi-layered p2p systems. The simulator is written in Java, is event-based and mainly used in p2p research projects. The main development of PeerfactSim.KOM started in 2005 and is driven since 2006 by the project “QuaP2P”,which aims at the systematic improvement and benchmarking of p2p systems. Further users of the simulator are working in the project “On-the-ﬂy Computing” aiming at researching p2p-based service oriented architectures. Both projects state severe requirements on the evaluation of multi-layered and large-scale distributed systems. We describe the architecture of PeerfactSim.KOM supporting these requirements in Section II, present the workﬂow, selected experiences and lessons learned in Section III and conclude the overview in Section IV.

Corona: A Stabilizing Deterministic Message-Passing Skip List - Nesterenko, Mikhail; Mohd, Rizal; Scheideler, Christian (Proceedings of the 13th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
We present Corona, a deterministic self-stabilizing algorithm for skip list construction in structured overlay networks. Corona operates in the low-atomicity message-passing asynchronous system model. Corona requires constant process memory space for its operation and, therefore, scales well. We prove the general necessary conditions limiting the initial states from which a self-stabilizing structured overlay network in message-passing system can be constructed. The conditions require that initial state information has to form a weakly connected graph and it should only contain identiers that are present in the system. We formally describe Corona and rigorously prove that it stabilizes from an arbitrary initial state subject to the necessary conditions. We extend Corona to construct a skip graph.

Adaptives Loadbalancing für strukturierte Peer-to-Peer-Netzwerke am Beispiel von Chord - Wette, Philip

Algorithmische Grundlagen verteilter Speichersysteme - Meyer auf der Heide, Friedhelm; Scheideler, Christian (Informatik Spektrum)

Foreword - Gavoille, Cyril; Patt-Shamir, Boaz; Scheideler, Christian (Theory of Computing Systems)

Time Complexity of Distributed Topological Self-stabilization: The Case of Graph Linearization - Gall, Dominik; Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (LATIN 2010: Theoretical Informatics, 9th Latin American Symposium, Oaxaca, Mexico, April 19-23, 2010. Proceedings)

Brief announcement: towards robust medium access in multi-hop networks - Richa, Andrea W.; Zhang, Jin; Scheideler, Christian; Schmid, Stefan (Proceedings of the 29th Annual ACM Symposium on Principles of Distributed Computing, PODC 2010, Zurich, Switzerland, July 25-28, 2010)

A Jamming-Resistant MAC Protocol for Multi-Hop Wireless Networks - Richa, Andrea W.; Scheideler, Christian; Schmid, Stefan; Zhang, Jin (Distributed Computing, 24th International Symposium, DISC 2010, Cambridge, MA, USA, September 13-15, 2010. Proceedings)

Brief Announcement: Stabilizing Consensus with the Power of Two Choices - Doerr, Benjamin; Ann Goldberg, Leslie; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Distributed Computing, 24th International Symposium, DISC 2010, Cambridge, MA, USA, September 13-15, 2010. Proceedings)

Algorithms for Sensor Systems - 6th International Workshop on Algorithms for Sensor Systems, Wireless Ad Hoc Networks, and Autonomous Mobile Entities, ALGOSENSORS 2010, Bordeaux, France, July 5, 2010, Revised Selected Papers

Foreword - D. Kleinberg, Robert; Scheideler, Christian (Theory Comput. Syst.)

Towards a Scalable and Robust DHT - Awerbuch, Baruch; Scheideler, Christian (Theory Comput. Syst.)

Robust random number generation for peer-to-peer systems - Awerbuch, Baruch; Scheideler, Christian (Theor. Comput. Sci.)

A Distributed and Oblivious Heap - Scheideler, Christian; Schmid, Stefan (Automata, Languages and Programming, 36th Internatilonal Colloquium, ICALP 2009, Rhodes, Greece, July 5-12, 2009, Proceedings, Part II)

A Self-stabilizing and Local Delaunay Graph Construction - Jacob, Riko; Ritscher, Stephan; Scheideler, Christian; Schmid, Stefan (Algorithms and Computation, 20th International Symposium, ISAAC 2009, Honolulu, Hawaii, USA, December 16-18, 2009. Proceedings)

A distributed polylogarithmic time algorithm for self-stabilizing skip graphs - Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (Proceedings of the 28th Annual ACM Symposium on Principles of Distributed Computing, PODC 2009, Calgary, Alberta, Canada, August 10-12, 2009)

A DoS-resilient information system for dynamic data management - Baumgart, Matthias; Scheideler, Christian; Schmid, Stefan (SPAA 2009: Proceedings of the 21st Annual ACM Symposium on Parallelism in Algorithms and Architectures, Calgary, Alberta, Canada, August 11-13, 2009)

Brief Announcement: On the Time Complexity of Distributed Topological Self-stabilization - Gall, Dominik; Jacob, Riko; W. Richa, Andrea; Scheideler, Christian; Schmid, Stefan; Täubig, Hanjo (Stabilization, Safety, and Security of Distributed Systems, 11th International Symposium, SSS 2009, Lyon, France, November 3-6, 2009. Proceedings)

Stabilizing Consensus with the Power of Two Choices - Doerr, Benjamin; Ann Goldberg, Leslie; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Algorithmic Methods for Distributed Cooperative Systems, 06.09. - 11.09.2009)

An O(log n) dominating set protocol for wireless ad-hoc networks under the physical interference model - Scheideler, Christian; W. Richa, Andréa; Santi, Paolo (Proceedings of the 9th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2008, Hong Kong, China, May 26-30, 2008)

Algorithms for Overlay Networks - Scheideler, Christian (Bulletin of the EATCS)

A jamming-resistant MAC protocol for single-hop wireless networks - Awerbuch, Baruch; W. Richa, Andréa; Scheideler, Christian (Proceedings of the Twenty-Seventh Annual ACM Symposium on Principles of Distributed Computing, PODC 2008, Toronto, Canada, August 18-21, 2008)

SPREAD: an adaptive scheme for redundant and fair storage in dynamic heterogeneous storage systems - Mense, Mario; Scheideler, Christian (Proceedings of the Nineteenth Annual ACM-SIAM Symposium on Discrete Algorithms, SODA 2008, San Francisco, California, USA, January 20-22, 2008)

Tiara: A Self-stabilizing Deterministic Skip List - Clouser, Thomas; Nesterenko, Mikhail; Scheideler, Christian (Stabilization, Safety, and Security of Distributed Systems, 10th International Symposium, SSS 2008, Detroit, MI, USA, November 21-23, 2008. Proceedings)

Broadcasting: Wie verbreite ich schnell Informationen? - Scheideler, Christian (Taschenbuch der Algorithmen)

INFORMATIK 2008, Beherrschbare Systeme - dank Informatik, Band 1, Beiträge der 38. Jahrestagung der Gesellschaft für Informatik e.V. (GI), 8. - 13. September, in München, Deutschland

Taschenbuch der Algorithmen - Vöcking, Berthold; Alt, Helmut; Dietzfelbinger, Martin; Reischuk, Rüdiger; Scheideler, Christian; Vollmer, Heribert; Wagner, Dorothea

Algorithms for Fault-Tolerant Routing in Circuit-Switched Networks - Bagchi, Amitabha; Chaudhary, Amitabh; Scheideler, Christian; Kolman, Petr (SIAM J. Discrete Math.)

Linearization: Locally Self-Stabilizing Sorting in Graphs - Onus, Melih; W. Richa, Andrea; Scheideler, Christian (Proceedings of the Nine Workshop on Algorithm Engineering and Experiments, ALENEX 2007, New Orleans, Louisiana, USA, January 6, 2007)

Towards Scalable and Robust Overlay Networks - Awerbuch, Baruch; Scheideler, Christian (6th International workshop on Peer-To-Peer Systems, IPTPS 2007, Bellevue, WA, USA, February 26-27, 2007)

A denial-of-service resistant DHT - Awerbuch, Baruch; Scheideler, Christian (Proceedings of the Twenty-Sixth Annual ACM Symposium on Principles of Distributed Computing, PODC 2007, Portland, Oregon, USA, August 12-15, 2007)

A Denial-of-Service Resistant DHT - Awerbuch, Baruch; Scheideler, Christian (Distributed Computing, 21st International Symposium, DISC 2007, Lemesos, Cyprus, September 24-26, 2007, Proceedings)